2021
DOI: 10.1002/cbm.2210
|View full text |Cite
|
Sign up to set email alerts
|

External locus of control and cognitive ability independently distinguish men in prison from community living non‐offending men

Abstract: Background The ability to cope with failure and subsequent feedback is crucial for prisoner rehabilitation. Impaired executive function in prisoners, high trait aggression and external locus of control can undermine the capacity to react to feedback in socially adaptive ways. Aim To investigate the relationships between aggression, locus of control, and attribution in an experimental task involving feedback about failure and success. Methods Two groups were compared: 1. Imprisoned men, 2. Community living men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The former is called internal attribution and the latter is called external attribution ( 10–12 ). Fontao and Ross ( 13 , 14 ) found that external attributional biases was associated to aggressive behaviors. The overuse of external attribution brought about higher levels of aggression.…”
Section: Introductionmentioning
confidence: 99%
“…The former is called internal attribution and the latter is called external attribution ( 10–12 ). Fontao and Ross ( 13 , 14 ) found that external attributional biases was associated to aggressive behaviors. The overuse of external attribution brought about higher levels of aggression.…”
Section: Introductionmentioning
confidence: 99%